Pengaruh Desain Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Sepatu Ventela : (Studi Kasus Pada Mahasiswa Universitas Bhayangkara Jakarta Raya) - Willson, Michael Aris; Komariah, Neng Siti; Anas, Haryudi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The growth of the local fashion industry in Indonesia has shown significant progress, driven by increasing consumer preference for domestic products. One of the emerging local brands is Ventela, a footwear company that emphasizes the strength of its product design and quality. This study aims to: (1) examine the influence of product design on purchasing decisions of Ventela shoes, (2) analyze the impact of product quality on purchasing decisions, and (3) assess the combined effect of product design and quality on purchasing decisions. A quantitative research method was employed, with data collected through an online questionnaire distributed to 171 students from the Management Study Program, Class of 2021, at Universitas Bhayangkara Jakarta Raya. Data analysis was conducted using SPSS version 26. The results indicate that product design attracts consumers through visual appeal and comfort, while product quality builds trust and satisfaction. Simultaneously, both product design and quality significantly influence purchasing decisions. These findings highlight the importance of product innovation and quality improvement strategies in strengthening the competitiveness of local brands in the increasingly competitive fashion industry.